Phytochemical Composition And In Vitro Antifungal Limitations Of Salacca Zalacca Peel Extract Against Candida Albicans - Aryasa, Mahesa Ajisaka; Mahendra, Agung Nova; Ernawati, Desak Ketut; Satriyasa, Bagus Komang (Jurnal Locus Penelitian dan Pengabdian, 2026)
Candidiasis, primarily caused by Candida albicans, continues to pose clinical challenges due to antifungal resistance and the adverse effects of synthetic agents. This study aimed to evaluate the phytochemical profile and antifungal efficacy of Salacca zalacca (Bali snakefruit) peel extract as a potential natural alternative. The extract was obtained using ethanol-based maceration and analyzed through UV-Vis spectrophotometry. The results revealed high concentrations of flavonoids (857.59 mg/100 g), phenolics (860.54 mg/100 g), vitamin C (8391.10 mg/100 g), and tannins, along with the qualitative presence of saponins. Antioxidant analysis indicated weak radical scavenging activity (IC?? = 546.19 ppm) but a high total antioxidant content (2532.17 mg GAE/L). Antifungal testing using the disk diffusion method against C. albicans showed no inhibition zones at extract concentrations of 2.5%, 5%, and 10%, whereas the ketoconazole control produced a strong inhibition zone (mean 20.33 mm). The lack of activity may be attributed to diffusion limitations or solubility issues rather than the absence of bioactive compounds. Despite the negative antifungal results, the high phytochemical content suggests potential for alternative therapeutic applications. Further studies employing alternative solvents, higher extract concentrations, and more sensitive antifungal assays are recommended.